An overview of “arginussa” species group of Memphis Hübner, [1819], with the description of a new species from Panama (Lepidoptera: Nymphalidae: Charaxinae) - Dias, Fernando M. S.; Riley, Thomas J.; Casagrande, Mirna M.; Mielke, Olaf H. H. (Zootaxa, 2021)
Memphis Hübner, [1819] is a nymphalid butterfly genus exclusive to the Neotropics. It includes species with iridescent bluish or greenish coloration on the upper side of the wings while the underside is cryptic, resembling dead leaves. This paper aims to describe a remarkable new species, M. smalli Riley & Dias sp. nov., from the remote Atlantic slopes of Panama based on molecular and morphological analyses. We also review the taxonomy of species herein included in the “arginussa” species group based on distances analyses of DNA sequence data. The “arginussa” species group, as defined here, includes M. arginussa (Geyer, 1832), M. eubaena (Boisduval, 1870) stat. rest., M. onophis (Felder & Felder, 1861) stat. rest., M. lemons (Druce, 1877), M. neidhoeferi (Rotger, Escalante & Coronado, 1965), M. perenna (Godman & Salvin, [1884]), M. lankesteri (Hall, 1935) stat. rest., M. paulus Costa & Orellana, 2014, M. pithyusa (Felder, 1869), M. herbacea (Butler & Druce, 1872) and M. smalli sp. nov. Anaea pithyusa morena Hall, 1935 syn. nov. is recognized as a synonym of Nymphalis pithyusa Felder, 1869. The new species and its closest ally, M. herbacea, are illustrated, including characters of the head, labial palpus, wings, legs, male and female genitalia and their distribution map.